Satisfaction of Parents towards Early Childhood Education Provision of Banchauat School Chauat District Nakhon Si Thammarat Province - Chaiduang, Natharod; Lehmongkol, Pattamavadi; Hirunchalothorn, Piyanan (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purpose of this research was to study the satisfaction of parents towards early childhood education provision of Banchauat School Chauat District Nakhon Si Thammarat Province in learning experience, role of teachers, environmental provision, service and relationship between school and community. The population of this study was 121 preschool parents from kindergarten level 1-3 of Banchauat School Chauat District Nakhon Si Thammarat Province in the 2019 academic year. The instrument tool was a questionnaire. Percentage, mean and standard deviation were used to analyze data. The research results founded that satisfaction of parents towards early childhood education provision of Banchauat School Chauat District Nakhon Si Thammarat Province were at high level in all five aspects.These aspects were in role of teachers (µ=4.32, σ=0.62), learning experience (µ=4.17, σ=0.65), environmental provision (µ=4.14, σ=0.66), service (µ=4.09, σ=0.69) and relationship between school and community (µ=3.99, σ=0.69) respectively.